The Autonomic Regulation of Tumor Growth and the Missing Links - Bautista, Maricris; Krishnan, Anand (Frontiers in Oncology, 2020)
Accumulating evidence now indicates that peripheral nerves and solid tumors mutually support each other. The tumor-derived molecular cues guide nerves to infiltrate the tumor milieu, while nerve-secreted molecules promote tumor growth and dissemination. In this mini review, we discuss the unique roles of sympathetic and parasympathetic nerves in promoting tumor growth and metastasis. The specific contribution of adrenergic and cholinergic signals, the receptors involved, and the downstream molecular links in cancer and stromal cells are discussed with respect to their ability to modulate tumor growth. We identified underscored niche areas in the field, an investigation of which is critical to fill the knowledge gap in understanding the biology of neuromodulation of cancers.